Product Heterogeneity, Cross-Country Taste Differences, and the Consumption Home Bias - Raphael A. Auer (Swiss National Bank, Study Center Gerzensee, 2013)
This paper starts by showing that in the European car industry, there exist cross-country taste differences along the product attribute dimension that significantly drive net trade patterns and reduce the volume of trade. Further it is shown that, after the creation of the European common market, these cross-country taste differences caused a sluggish response of trade volume to liberalization as it took time for each country's industry structure to adapt to the demand structure of the common market. To rationalize such trade patterns, a structural model of demand featuring consumers with homothetic preferences and heterogeneous tastes over attributes is developed. Allowing for international trade, the model predicts that consumption is home-biased in the immediate aftermath of trade liberalization since each country's industry structure is optimized for the preferences of domestic consumers and domestic output thus does not match well with preferences abroad. Along the transition to the open economy steady state, each country's industry specializes into market segments with comparatively large domestic demand, implying that domestic firms leave the market segments the foreign industry specializes in. This increasing specialization that underlies the "home market" effect increases the average demand for foreign goods, the volume of trade, and the average gains from liberalization.
Keywords: F12; F15; L15; L16; 330; Intra-industry trade; Monopolistic competition; Product heterogeneity; Industrial structure; Firm dynamics; Produktdifferenzierung; Intraindustrieller Handel; Unternehmenserfolg; Industriestruktur; Privater Konsum; Monopolistischer Wettbewerb; Theorie